PEMBELAJARAN TAHFIZ BERBASIS PENGULANGAN AYAT DALAM MENINGKATKAN KUALITAS HAFALAN AL-QURAN: STUDI KASUS DI SMP AN-NUR PRIMA MEDAN - Fedian, Imelda; Juli Julaiha P (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this research is to examine how the verse repetition method is applied in the tahfiz learning process at SMP An-Nur Prima Medan, explore the factors that facilitate and hinder its implementation, and develop a conceptual framework of tahfiz instruction based on empirical findings from the field. A qualitative case study approach was adopted to gain an in-depth understanding of the learning process. Data collection was conducted between May 25 and June 2, 2026, through classroom observations, semi-structured interviews, and document analysis. The participants included the school principal, the coordinator of the Al-Qur’an tahfiz program, and fourteen students from the eighth grade. The collected data were examined using the interactive analysis procedure proposed by Miles, Huberman, and Saldaña, encompassing data condensation, data presentation, and conclusion verification. The results indicated that tahfiz learning at SMP An-Nur Prima implements tikrar (repetition) integrated with talaqqi, itqan, memorization deposits (setoran), tasmi’, and muraja’ah. The implementation is oriented toward memorization quality (mutqin) through a continuous repetition system. The primary supporting factors include institutional support, teacher competence, the school's Qur'anic culture, and parental involvement, while the inhibiting factors include burnout due to repetition, gadget distractions, time constraints, and differences in students' abilities. This study generates the Verse-Repetition-Based Tahfiz Model, demonstrating that the success of a tahfiz program in formal schools is determined by the integration of talaqqi, tikrar, itqan, evaluation, and muraja’ah within a structured and sustainable learning system.